Patterns of Cephalic and Facial Indices in Three Ethnic Groups in Rural Population of Banke District of Nepal - Jihan, Prasad Ram; Kumar, Singh Manish; Rajesh, Das; Mangesh, Bajracharya; Kumar, Gupta Anil (Med Phoenix, 2019)
Abstract available with the full text.